High efficient fire-retardant coatings on wood fabricated by divalent metal ion cross-linked multilayer polyethyleneimine and ammonium polyphosphate polyelectrolytes. (October 2022) - Dong, Sijie; Jiang, Haochong; Hou, Bohan; Du, Yuting; Jin, Chunde; Yan, Yutao
Highlights: Divalent metal ions cross-linked PEI-APP coating was successfully constructed on wood; Divalent metal ions had good synergy effects with PEI-APP in improving wood fire resistance; Divalent metal ions could accelerate the char-forming process and increase the amount of carbon formed; The green and low-cost flame-retardant treatment approach is likely to improve the added-value of modified wood and promote its wide application. Abstract: In this work, to endow wood with efficient flame retardancy, polyethyleneimine (PEI) and ammonium polyphosphate (APP) as an intumescent flame retardant system was deposited on wood via layer-by-layer (LbL) self-assembly approach combined with divalent metal ions cross-linking treatment. Scanning electron microscopy equipped with energy-dispersive (SEM-EDX) and Fourier transform infrared spectroscopy (FT-IR) analysis demonstrated that divalent metal ions cross-linked PEI-APP coatings were successfully constructed on wood surface. Thermogravimetric analysis (TGA) indicated that PEI-APP modification could improve the thermal stability of coated wood by decreasing the maximum degradation rate and increasing the char residue, while Cu 2+ and Co 2+ cross-linking treatments could further enhance these properties. What's more, the fire resistance of the modified wood was also significantly improved, proved by limiting oxygen index (LOI) and cone calorimeter characterizations. When coated by PEI-APP, the LOI was increased to 37.5 from the pristine uncoated 23.5. Further, when cross-linked by Cu 2+ and Co 2+, the LOIs were increased to 47 and 42.5, respectively. In addition, the heat release rate (HRR) and total heat release (THR), especially the total smoke release of the PEI-APP and metal ions cross-linked coated wood, were also obviously decreased. The improvement of thermal stability and fire-retardant performance was mainly due to the synergistic effect of APP and metal ions, which could accelerate the char-forming process and increase the amount of carbon formed, thus effectively preventing the spread of heat and flame into the inner wood and protecting the wood from fire attacking. The green and low-cost flame-retardant treatment approach reported in this study is likely to improve the added value of modified wood and promote its wide application.